Comparison of the Effects of TIPS versus BRTO on Bleeding Gastric Varices: A Meta-Analysis - Zi Wen Wang; Jin Chao Liu; Fang Zhao; Wen Guang Zhang; Xu Hua Duan; Peng Fei Chen; Si Fu Yang; Hong Wei Li; Fu Wen Chen; Hong Sheng Shi; Jian Zhuang Ren (Canadian Journal of Gastroenterology and Hepatology)
Background and Aim. Upper gastrointestinal bleeding is a threat to patients with gastric varices (GVs). Previous studies have concluded that both transjugular intrahepatic portosystemic shunt (TIPS) and balloon-occluded retrograde transvenous obliteration (BRTO) are effective treatments for patients with GV. We aimed to compare the efficiency and outcomes of these two procedures in GV patients through meta-analysis. Methods. The PubMed, Cochrane Library, EMBASE, and Web of Science databases were searched using the keywords: GV, bleeding, TIPS, and BRTO to identify relevant randomized controlled trials and cohort studies. The overall survival (OS) rate, imminent haemostasis rate, rebleeding rate, technical success rate, procedure complication rate (hepatic encephalopathy and aggravated ascites), and Child-Pugh score were evaluated. Randomized clinical trials and cohort studies comparing TIPS and BRTO for GV due to portal hypertension were included in our meta-analysis. Two independent reviewers performed data extraction and assessed the study quality. A meta-analysis was performed to calculate risk ratios (RRs), mean differences (MDs), and 95% CIs using random effects models. Results. A total of nine studies fulfilled the inclusion criteria. There was a significant difference between TIPS and BRTO in the OS rate (RR, 0.81 (95% CI, 0.66 to 0.98); P=0.03) and rebleeding rate (RR, 2.61 (95% CI, 1.75 to 3.90); P<0.00001). TIPS had a higher incidence rate of hepatic encephalopathy (RR, 16.11 (95% CI, 7.13 to 36.37); P<0.00001). There was no significant difference between TIPS and BRTO in the immediate haemostasis rate (RR, 0.99 (95% CI, 0.89 to 1.10); P=0.84), technical success rate (RR, 1.06 (95% CI, 0.98 to 1.16); P=0.16), aggravated ascites rate (RR, 0.60 (95% CI, 0.33 to 1.09); P=0.10), or Child-Pugh change (MD, 0.22 (95% CI, −0.21 to 0.65); P=0.31). Conclusions. In this meta-analysis, BRTO brought more benefits to patients, with a higher OS rate and lower rebleeding rate. BRTO is a feasible method for GVB.